Menstrual hygiene knowledge, attitudes, and practices among college students in Mohanpur, West Tripura, India: A cross-sectional study (International Journal of Food and Nutritional Sciences, 2023)
It is important to follow safe hygienic practices during menstruation, such as washing the genital area and using hygienic sanitary napkins. Aims and objectives: The purpose of this study is to assess the awareness level, practices, and attitudes of college students in West Tripura regarding menstrual hygiene.Materials and Method: In Mohanpur, West Tripura, 100 college girls participated in a cross-sectional study. Simple proportions and Chi-square tests were used to analyze the data collected by a pretested questionnaire. Result : Menstruation was untaught to 32 percent of girls before menarche. The mean age of menarche is 13 years, ranging from 10 to 16 years. 66% of students reported their mothers taught them menstrual habits, 53% used sanitary napkins or a similar absorbent material during their menstrual cycle, and 47% washed their genital areas regularly. Premenstrual symptoms were reported by 83% of girls, 70% of whom had regular periods. The myths surrounding menstruation have affected 77% of girls. Menstrual restrictions were enforced on 82% of girls. Conclusion : Developing countries like India need to strengthen their menstrual management programs. A combination of educational television programs, health personnel awareness programs, and government and non-governmental organizations intervention is required.